Netralitas Aparatur Sipil Negara Dalam Pemilihan Umum Tahun 2019 Di Provinsi Banten (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2020)
This study aims to determine how the Neutrality Of The State Civil Apparatus In The 2019 General Election In Banten Province and to find out what are the supporting factors and inhibiting factors. The research method used in the research is a qualitative descriptive method using purposive sampling technique then the data collection technique is by interview and documentation. The result of this study indicate that the Neutrality Of The State Civil Apparatus In The 2019 General Election In Banten Province has not gone well, because there are still Civil Apparatus Of The Banten Provincial goverment that are not neutral by supporting one of the candidates for the Regional Representative Council and one of the candidates for Presiden/Vice President. The inhibiting factor of the neutrality of the State Civil Apparatus in the 2019 general election in Banten Province is caused by the mindset that has not yet been formed, the existence of kindship relations and sanctions that are still weak. Therefore, the Banten Provincial government needs to incrase supervision, guidance, and provide strict sanctions for state Civil Apparatus that are not Neutral In The 2019 General Election.